Secondary School Teachers’ Resiliency Amidst COVID 19 Pandemic - Jonifer Dultra; Maricel Abarca; Agnes Bulado; Maria Socorro Dultra (Newinera Publisher, 2022)
Achieving quality education is nonetheless the welfare among teachers. This study ascertains the effectiveness of Mindful Awareness Training among teacher-leaders resiliency in public secondary schools in the Philippines amidst pandemics. The participants of this study were subjected to a 10-minute training of mindful awareness at their own convenient time each day that is good for one week. They were asked to give their opinion before and after the training to determine the effectiveness of the said model. This study is a one-group quantitative design and utilized descriptive and non-parametric analyses. It found that Mindful Awareness Training is effective in the development of teachers’ resiliency levels. It helps teachers to boost their confidence in facing pandemic crises like COVID-19.